Exploring Conspicuous Luxury Consumption In Iran: The Role Of Individual Factors and Consumer Knowledge - Kermani, Mohammad (Université d'Ottawa / University of Ottawa, 2017)
This research tested a conceptual model predicting the propensity to engage in two distinct forms of conspicuous consumption (bandwagon and snob consumption) that was developed by Kastanakis and Balabanis (2014) in a collectivistic Iranian context. This study found that this conceptual model was more successful in accounting for the variance in bandwagon consumption (i.e., conformity seeking conspicuous luxury consumption) than snob consumption (i.e., uniqueness seeking conspicuous luxury consumption) in the Iranian context. In addition to status seeking, it was found that consumer susceptibility to normative influence (CSNI) and consumer need for uniqueness (CNFU) mediates the influence of self-concept on bandwagon consumption. This finding suggests that the relationship between snob consumption and CNFU may differ in the Iranian context. Results also show that the relationships between CSNI, unpopular counter choice conformity (a sub-construct of CNFU) and status seeking with bandwagon consumption were all negatively moderated by consumer knowledge for fashion luxury goods. These findings extend the original conspicuous consumption model and provide some insight for the development of marketing strategies in Iran.
Keywords: Conspicuous consumption; Luxury; Status; Culture; Iranian; Bandwagon consumption; Snob consumption; Consumer Knowledge